Painless Urethral Bleeding During Penile Erection in an Adult Man With Klippel-Trenaunay Syndrome: A Case Report. Issue 2 (13th February 2018) - Lei, Hongen; Guan, Xing; Han, Hu; Qian, Xiaosong; Zhou, Xiaoguang; Zhang, Xiaodong; Tian, Long
Abstract: Introduction: Klippel-Trenaunay syndrome (KTS) is a rare congenital vascular disorder characterized by a triad of cutaneous port wine capillary malformations, varicose veins, and hemihypertrophy of bone and soft tissues. Aims: To report on a rare case of KTS in an adult man manifested by painless urethral bleeding during penile erection briefly review the clinical presentation and management of the genitourinary forms of this syndrome. Methods: On presentation, the clinical features of this patient, including medical history, signs and symptoms, and imaging examinations, were recorded. After diagnosis and initial treatment, a literature review of the urethral features of KTS was performed and is discussed in this report. Results: A 35-year-old man with KTS presented with painless urethral bleeding during penile erection that was associated with posterior urethral vascular malformations. The coagulation method was used to treat the malformation, and no urethral bleeding or gross hematuria occurred during a postoperative follow-up period of 6 months. Conclusion: This case demonstrates that coagulation therapy and careful follow-up can be adequate treatment approaches for urethral features of KTS. However, the long-term efficacy of coagulation for this disorder should be investigated further.